Emile Durkheim's Theory of Social Facts on Moral and Character Education - Irmawati Musa (Kirana Publisher (KNPub), 2024)
Character education has been carried out for a long time, but over time it has been eroded by modernization. Morals are provisions for developing oneself. Moral problems are problems that concern humans everywhere, both in advanced societies and in underdeveloped societies. This is because one person's moral damage disturbs the peace of others. The aim of this research is to determine moral education and individual character based on Emile Durkheim's theory of social facts. The research method used is a qualitative method and the data collection technique is using library research. The results of this research show that Durkheim suggested that social research, including educational research, should be carried out based on empirical standards, with social facts as the main focus. Durkheim believed that morality is the result of social interaction between individuals and collective consciousness. Character education is education that develops good character.